Functionalized Transparent Surfaces with Enhanced Self‐Cleaning against Ink Aerosol Contamination. Issue 1 (26th October 2016) - Noyan, Mehmet A.; Guilhot, Denis; Pruneri, Valerio
Abstract : During operation of a standard commercial inkjet printer, suspended ink particles form an ink aerosol inside the printing chamber that can cause serious malfunctions, including contamination of the transparent window of the printhead position calibration optical sensors. In this work, transparent conducting film (TCF) and surface functionalization through self‐assembled monolayer (SAM) are proposed and investigated to repel ink aerosol deposition on a transparent surface and to reduce its adverse effects. The results show that the combination of the Joule heating effect induced by applying an electrical current to the TCF and hydrophobic property of the SAM reduces transmittance loss from an average of 10% to less than 1.5%. Correspondingly, the area of the surface covered by ink decreases from 45.62% ± 6.15% to 1.71% ± 0.25%. The preliminary results are obtained with glass substrates and subsequently extended to the plastic window of a commercial inkjet printer calibration sensor, thus demonstrating the potential of the proposed approach to reduce aerosol contamination in real applications. Abstract : The combination of joule heating through transparent conductive film and hydrophobicity of self‐assembled monolayers creates a transparent surface capable of significantly reducing aerosol contamination. The research is relevant for consumer inkjet printers where aerosol contamination can cause serious malfunctioning of various parts, such as calibration sensors.